Assessing the time dependence of prognostic values of cytology and human papillomavirus testing in cervical cancer screening. Issue 10 (21st January 2019) - Isidean, Sandra D.; Wang, Yishu; Mayrand, Marie‐Hélène; Ratnam, Sam; Coutlée, François; Franco, Eduardo L.; Abrahamowicz, Michal; ,
Abstract : Accurate assessment of risks for developing cervical intraepithelial neoplasia of grade 2 or worse (CIN2+) after a given set of screening test results is instrumental to reaching valid conclusions and informing cervical cancer screening recommendations. Using data from the Canadian Cervical Cancer Screening Trial (CCCaST), we assessed prognostic values of enrollment screening test results to predict CIN2+ among women attending routine cervical screening using multivariable Cox proportional hazards (PH) regression and its flexible extension during each of two follow‐up periods (protocol‐defined and extended). Nonproportional (time‐dependent (TD)) and/or nonlinear effects were modeled, as appropriate. Women with abnormal cytology had hazard ratios (HRs) for CIN2+ detection of 17.61 (95% CI: 11.25–27.57) and 10.46 (95% CI: 5.41–20.24) relative to women with normal cytology during the protocol‐defined and extended follow‐up periods, respectively. High‐risk human papillomavirus (HR‐HPV) positivity was an even stronger predictor of CIN2+ risk, with significant TD effects during both follow‐up periods ( p <0.001 for both TD effects). Risks among women co‐testing HR‐HPV+ with and without abnormal cytology (relative to women co‐testing negative) were highest immediately after baseline, and decreased significantly thereafter ( p <0.001 for both TD effects). HRs for HPV16+ and HPV18+ women (relative to those testing HR‐HPV‐) did not vary significantly over time (HR = 182.96; 95% CI: 95.16–351.77 and HR = 111.81; 95% CI: 44.60–280.31, respectively). Due to TD effects, conventional Cox model estimates considerably underestimated adjusted HRs associated with positive HR‐HPV testing results early on in the follow‐up periods. Abstract : What's new? Advances to ensure the accurate assessment of cervical screening test results, whereby valid conclusions are made regarding cervical disease risk, are critical for improving screening recommendations. Here, using a novel flexible multivariable modeling technique for prognostic evaluation, the authors show that only positivity for high‐risk human papillomaviruses (HR‐HPVs), particularly HPV16/18, is a long‐term predictor of cervical disease. Short‐term risk associated with existing cervical lesions was predicted by abnormal cytology, genotype‐specific, and HR‐HPV testing results. Moreover, in a direct comparison, the alternative modeling technique revealed violations of the proportional hazards (PH) assumption associated with conventional Cox PH modeling for prognostic evaluation.